SCS205 Riqueza: Carioca common bean cultivar for Southern Brazil - Kavalco, Sydney Antonio Frehner; Nicknich, Waldir; Höfs, Alberto; Hemp, Silmar; Vogt, Gilcimar Adriano; Backes, Rogério (Agropecuária Catarinense, 2017)
Abstract – Santa Catarina Agricultural Research and Rural Extension Company (Epagri) developed the SCS205 Riqueza bean cultivar, of the carioca seed group. This new cultivar has excellent grain yield, high sanity, with a high grain weight associated with precocity. The plants are semi-erect with undetermined growth habit, adapted to mechanical harvesting. Resumo – A Epagri desenvolveu o cultivar de feijão SCS205 Riqueza, do grupo carioca. Este novo cultivar tem um excelente rendimento de grão, alta sanidade, com alto peso de grão associado com precocidade. As plantas são semi eretas com hábito de crescimento indeterminado, adaptadas à colheita mecânica.